CA125 is a potential biomarker to predict surgically incurable gastric and cardia cancer: A retrospective study. Issue 51 (December 2016) - Luo, Taobo; Chen, Wenhu; Wang, Lifang; Zhao, Hongguang
Abstract : Abstract: Preoperative evaluation of the curability of gastric and cardia cancer is important to avoid risks of unnecessary surgery. Our previous study has reported several clinical parameters associated with incurable gastric surgery. In this study, we aimed to evaluate the correlation between CA125 and the curability of gastric and cardia cancer. A total of 297 cases of gastric and cardia cancer were analyzed retrospectively, including 153 cases with radical surgery and 144 with surgery for incurable gastric or cardia cancer. χ 2 test was performed to analyze the associations between curability or incurable factors and clinicopathological data, including CA125 value. ROC curves were generated, and cutoff points for curability, T status, N status, peritoneal metastasis, and distant metastasis were found, respectively. Binary logistic regression was performed to verify the associations between dependent variables (curability, T status, N status, peritoneal metastasis, and distant metastasis) and covariates (related clinicopathological data from step 1 and cutoff points from step 2). Esophageal involvement, T grade, and CA125 were risk factors of curability. T grade and Borrmann type were risk factors of T status. T grade and CA125 were risk factors of N status. Age, esophageal involvement, T grade, and CA125 were risk factors of peritoneal metastasis. CA125 was risk factor of distant metastasis. CA125 is a potential biological marker for curability prediction of gastric and cardia cancer.